Hawthorn (Crataegus monogyna) Phenolic Extract Modulates Lymphocyte Subsets and Humoral Immune Response in Mice - Lis, Magdalena; Szczypka, Marianna; Suszko-Pawłowska, Agnieszka; Sokół-Łętowska, Anna; Kucharska, Alicja; Obmińska-Mrukowicz, Bożena (Planta Medica, 2020)
This study investigated the effect of hawthorn (Crataegus monogyna) phenolic extract on lymphocyte subsets in the lymphoid organs in nonimmunized mice and on humoral immune response in sheep red blood cell-immunized mice. Hawthorn phenolic extract (50, 100, 200 mg/kg) was administered orally five or ten times. Sheep red blood cells were injected 24 h after administration of the last extract dose. The lymphocyte subsets were assessed 24 and 72 h after the last dose. Humoral immune response was determined 4 and 7 days after immunization. Five doses of the extract decreased the percentage of CD4−CD8− and CD4+ thymocytes but elevated the percentage of CD4+CD8+ and CD8+ thymic cells. The extract increased the total number, percentage, and absolute count of T and B splenocytes. When administered five times, it lowered the percentage of T lymphocytes, but boosted the population of B lymphocytes of mesenteric lymph nodes (after 24 h). However, a rise in the population of T lymphocytes was observed 72 h after five and ten doses. The extract administered ten times elevated the number of plaque-forming cells and total anti-sheep red blood cell hemagglutinin titer but reduced the 2-ME-resistant antibody titer (day 7). At the same time, five doses of the extract increased antibody titers. Considering its impact on lymphocyte subsets and humoral immune response, hawthorn extract may be used as an immunomodulator.
Keywords: hawthorn; Crataegus monogyna; Rosaceae; lymphocyte; humoral immune response; mice